Jane B. – dwa portrety - Torzecki, Mateusz (Humaniora. Czasopismo Internetowe, 2025)
The text offers a cultural analysis of two cinematic portraits of Jane Birkin – actress, singer, and icon of popular culture – as created by Agnès Varda (Jane B. par Agnès V., 1988) and Charlotte Gainsbourg (Jane par Charlotte, 2021). These films approach Birkin from two distinct angles: one artistic, the other intimate and familial. The article compares strategies of representation and narrative constructions of identity, showing how intimacy and self-staging become tools for exploring femininity, memory, and transience. Both portraits are interpreted as dialogical forms of representation – not only of Birkin herself but also of the relationships between the filmmakers, the portrayed subject, and the viewers.